Boosting fish processing industry in India - K, Elavarasan; Ninan, George; N, Ravishankar C (Indian Farming, 2021)
Fish processing industry in India plays a vital role in the national economy and need to be boosted through strengthening various links between production and utilization. Increasing fish production, value addition, waste utilization, minimization of post-harvest loss, infrastructure establishments, and attitude changing are some of the key areas to be addressed for better fisheries resource utilization, enhancement of national food and nutritional security, assured livelihood of millions of population and overall socio-economic status.